Nanofluid Heat and Mass Transfer in Engineering Problems 2017
DOI: 10.5772/65556
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid with Colloidal Magnetic Fe3O4 Nanoparticles and Its Applications in Electrical Engineering

Abstract: In this study, we propose a new type of a cooling agent based on magnetic nanofluid for the purpose of replacing the classical cooling fluids in electrical power transformers. The magnetite (Fe 3 O 4 ) nanoparticles were synthesized by the co-precipitation method from an aqueous medium of salts FeCl 3 x6H 2 O and FeSO 4 x7H 2 O in the molar ratio Fe 3+ /Fe 2+ = 2:1, by alkalization with 10% aqueous solution of NaOH at 80°C, for 1 h. The size of the magnetite nanoparticles, as measured by X-ray diffraction meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…Magnetic nanofluids used as the core liquid in the micro-electric transformer obtained by coprecipitation method [27,35], is a colloidal suspension of nanoparticles of magnetite ( the synthesis procedure for obtaining magnetic nanofluids based on non-polar organic liquids are indicated in [28][29][30]35]. To be used as a transformer fluid core, magnetic nanofluid requires good colloidal stability and features adapted to the operating conditions and materials it is in contact with.…”
Section: Magnetic Nanofluids Used For Planar Microtransformers With Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic nanofluids used as the core liquid in the micro-electric transformer obtained by coprecipitation method [27,35], is a colloidal suspension of nanoparticles of magnetite ( the synthesis procedure for obtaining magnetic nanofluids based on non-polar organic liquids are indicated in [28][29][30]35]. To be used as a transformer fluid core, magnetic nanofluid requires good colloidal stability and features adapted to the operating conditions and materials it is in contact with.…”
Section: Magnetic Nanofluids Used For Planar Microtransformers With Cmentioning
confidence: 99%
“…An essential aspect is the complete coverage of NFM with stabilizer and the elimination of the primary non-adsorbed primary surfactant. Repeated flocculation/redispersing NFM's remain coated with the optimal amount of surfactant [34,35].…”
Section: Magnetic Nanofluids Used For Planar Microtransformers With Cmentioning
confidence: 99%
“…Currently, the efficiency of commercial solar PV solar panels is up to 15%, and most incoming solar radiation energy is either absorbed or reflected, and significant excess heat is dissipated and wasted. "To improve the efficiency of solar PVs, the novel concept of a photovoltaic-thermal solar panel hybrid system using nanofluids has been developed [25][26][27][28][29][30][31]. Regarding the PV-thermal solar hybrid system", references reported that "the solar irradiance is converted into electrical energy in the PV's cell; the excess thermal energy generated due to the intrinsic conversion efficiency limitation of the cell is dissipated into the water-based nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Lucian Pîslaru-Dănescu et al [26] proposed a new type of cooling agent based on magnetic nanofluid to replace the classical cooling fluids in electrical power transformers. Reference [26] presented a mathematical model and numerical simulation results that were very useful for investigating the heat transfer performances of magnetic nanofluid. Following that study, the cooling performance of this magnetic nanofluid was tested for two types of electrical power transformers and compared to classical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Si bien, el estudio de nanopartículas magnéticas (NPM) se ha enfocado en su síntesis y en la optimización de sus propiedades para mejorar elementos magnetoresistivos [1], [2], establecer la spintronica como nueva tecnología [3], para reemplazar líquidos de enfriamiento en transformadores de potencia eléctricos [4] o para aprovechar su afinidad superficial y usarlas en remediación ambiental, [5], en los últimos años se han abordado estudios sobre las aplicaciones de nanopartículas en medicina para el tratamiento y diagnósitico del cáncer, y han sido las nanopartículas óxidos de hierro (magnetita Fe 3 O 4 , maghemita γ-Fe 2 O 3 ) las que han tomado gran importancia en este tipo de aplicaciones, ya sea transportando fármacos [6], mejorando la calidad de imágenes médicas de diagnóstico [7], o usándose en procedimientos de teranostico: usos combinados tanto para terapia, detección y diagnóstico del cáncer [8], [9].…”
Section: Introductionunclassified